Enhanced proton conductivity in a flexible metal–organic framework promoted by single-crystal-to-single-crystal transformation. Issue 1 (9th December 2020) - Chen, Xi; Zhang, Zhongyue; Chen, Jin; Sapchenko, Sergei; Han, Xue; da-Silva, Ivan; Li, Ming; Vitorica-Yrezabal, Inigo J.; Whitehead, George; Tang, Chiu C.; Awaga, Kunio; Yang, Sihai; et al.
Abstract : Transformation of MFM-722(Pb)-DMA to MFM-722(Pb)-H2 O leads to an increase in proton conductivity linked to a structural transition. Abstract : MFM-722(Pb)-DMA undergoes a single-crystal-to-single-crystal (SCSC) transformation to give MFM-722(Pb)-H2 O via ligand substitution upon exposure to water vapour. In situ single crystal impedance spectroscopy reveals an increase in proton conductivity due to this structural transition, with MFM-722(Pb)-H2 O showing a proton conductivity of 6.61 × 10 −4 S cm −1 at 50 °C and 98% RH. The low activation energy ( E a = 0.21 eV) indicates that the proton conduction follows a Grotthuss mechanism.